2018
DOI: 10.1161/strokeaha.117.018063
|View full text |Cite
|
Sign up to set email alerts
|

Challenge and Yield of Enrolling Racially and Ethnically Diverse Patient Populations in Low Event Rate Clinical Trials

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00004732.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…According to the National Institutes of Health (NIH) [16,17], adequate enrollment and analysis plans related to racial and ethnic groups are essentially needed in clinical research, where the adequate enrollment could be determined by using the participation to prevalence ratio that is the percentage of BIPOC among trial participants divided by the percentage of BIPOC in the overall diabetes population [8]. Despite the importance of representative racial and ethnic enrollment, the current practice remained suboptimal in many randomized controlled trials (RCTs) including trials of cancer [18][19][20], stroke [21], systemic lupus erythematosus [22], cardiovascular disease [23][24][25][26][27], obesity [28], acute pain [29], coronavirus disease 2019 [30], and vaccine [31]. Likewise, one previously study reported that there were 62% and 78% of the diabetes RCTs conducted in the US and UK respectively under-enrolling the BIPOC groups [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Institutes of Health (NIH) [16,17], adequate enrollment and analysis plans related to racial and ethnic groups are essentially needed in clinical research, where the adequate enrollment could be determined by using the participation to prevalence ratio that is the percentage of BIPOC among trial participants divided by the percentage of BIPOC in the overall diabetes population [8]. Despite the importance of representative racial and ethnic enrollment, the current practice remained suboptimal in many randomized controlled trials (RCTs) including trials of cancer [18][19][20], stroke [21], systemic lupus erythematosus [22], cardiovascular disease [23][24][25][26][27], obesity [28], acute pain [29], coronavirus disease 2019 [30], and vaccine [31]. Likewise, one previously study reported that there were 62% and 78% of the diabetes RCTs conducted in the US and UK respectively under-enrolling the BIPOC groups [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our study provided a relatively unique opportunity to examine several social determinants as predictors of both consent to participate and retention as part of a prospective, longitudinal cohort study. Achieving and retaining a diverse group of participants within clinical trials has been a significant challenge reported in the literature ( 27 ). Barriers to recruitment and retention have included age, sex, socioeconomic factors, cultural factors, and practical challenges, including time and travel commitments ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a policy commitment by the National Institutes of Health (NIH) and the allocation of resources to address minority recruitment by the NIH, 10 the fewer revascularizations in Black and other minority populations is reflected in their lower recruitment to the NIH-funded clinical trials. 11 It is tempting to attribute the lower rates of revascularization in minority groups to a disparity in access to care, 7 with racial/ethnic differences in revascularizations persisting after adjustment for patient and hospital characteristics in some, 6,12 but not all, 5,13 reports. Lower rates of revascularization in minority populations persist in the Veterans Health Administration System, where access to care should not be an issue.…”
Section: Clinical and Population Sciencesmentioning
confidence: 99%
“…Despite major efforts to bolster recruitment of minority patients, the percent of Blacks has remained low in the NIH trials related to asymptomatic carotid disease. 11 An important goal should be recruitment proportionate to their representation among people with the disease. These data suggest that the goals for minority recruitment for studies of asymptomatic (ie, general population) high-grade carotid stenosis should be reconsidered.…”
Section: Clinical and Population Sciencesmentioning
confidence: 99%